TYRO3 blockade enhances anti-PD-1 therapy response by modulating expression of CCN1 in tumor microenvironment. Issue 1 (24th January 2023) - Park, Miso; Kuen, Da-Sol; Park, Jaewoo; Choi, Munkyung; Kim, Yeonji; Roh, Eun Chae; Choi, Yong June; Kim, Yoon Gyoon; Chung, Yeonseok; Cho, Sung Yun; Kang, Keon Wook
Abstract : Background: Immunological contexture differs across malignancies, and understanding it in the tumor microenvironment (TME) is essential for development of new anticancer agents in order to achieve synergistic effects with anti-programmed cell death protein-1 (PD-1) therapy. TYRO3, AXL, and MERTK receptors are bi-expressed in both cancer and immune cells, and thus emerge as promising targets for therapeutic intervention. Whereas AXL and MERTK have been extensively studied, the role of TYRO3, in the TME, is still undetermined. Methods: Here, we screened the TYRO3-focused chemical library consisting of 208 compounds and presented a potent and highly selective TYRO3 inhibitor, KRCT87. We explored the role of TYRO3 using mouse engrafting MC38 or 4T1 tumors. We validated the results using flow cytometry, RNA sequencing analysis, gene knockdown or overexpression, ex vivo immune cells isolation from mouse models, immunoblotting and quantitative PCR. Flow cytometry was used for the quantification of cell populations and immunophenotyping of macrophages and T cells. Co-cultures of macrophages and T cells were performed to verify the role of CCN1 in the tumors. Results: TYRO3 blockade boosts antitumor immune responses in both the tumor-draining lymph nodes and tumors in MC38-syngeneic mice models. Moreover, the combination of KRCT87 and anti-PD-1 therapy exerts significant synergistic antitumor effects in anti-PD-1-non-responsive 4T1-syngeneic model. Mechanistically, we demonstrated that inhibition of TYRO3-driven CCN1 secretion fosters macrophages into M1-skewing phenotypes, thereby triggering antitumor T-cell responses. CCN1 overexpression in MC38 tumors diminishes responsiveness to anti-PD-1 therapy. Conclusions: The activated TYRO3-CCN1 axis in cancer could dampen anti-PD-1 therapy responses. These findings highlight the potential of TYRO3 blockade to improve the clinical outcomes of anti-PD-1 therapy.